The social imperative in sustainable urban development: The case of Masdar City in the United Arab Emirates. Issue 2 (7th May 2019) - Randeree, Kasim; Ahmed, Nadeem
Abstract : Purpose: The purpose of this paper is to examine social sustainability effectiveness of eco-cities through the case of Masdar City's strategy for urban sustainability in Abu Dhabi, United Arab Emirates. Design/methodology/approach: Using a case study approach, the paper is an exploratory, qualitative analysis, which investigates the social, environmental and economic performance of Masdar City, a purported carbon-neutral, zero-waste urban development. Findings: Though Masdar City substantively contributes to innovation in sustainable urban development within environmental and economic contexts and has been effective in capital circulation in green technology markets, the impetus as a commercially driven enterprise is most evident. Successful sustainable urban development requires greater consideration for the social imperative. Practical implications: Eco-city mega-projects, such as Masdar City, have the potential to fuse achievements in innovation, technology and economic enterprise with the social imperative of functional urban habitats. Originality/value: Eco-cities are of increasing interest given the growing need for sustainable, energy-efficient living. This paper contributes through a novel case study, exploring how the concept of the eco-city has been developed and understood in the Masdar City context and discusses successes and deficits in its strategic implementation.